Freestanding Sodium-Ion Batteries Electrode Using Graphene Foam Coaxially Integrated with TiO2 Nanosheets. Issue 13 (7th October 2017) - Wu, Gaoxiang; Chen, Jiewei; Guo, Yanjiao; Li, Xiaodan; Luo, Bi; Chu, Lihua; Han, Yu; Jiang, Bing; Xu, Li; Li, Meicheng
Abstract : Sodium-ion batteries (SIBs) have attracted great interests for use as the large-scale rechargeable batteries, in which electrode materials are the most crucial components. Here, an ingenious programming of freestanding electrode material is reported for SIBs, which consists of titanium dioxide nanosheets aligned vertically on graphene foams (GF) framework inside and outside forming coaxial frame structure (GF-CF). This frame architecture not only ensures sufficient contact area between active materials and electrolyte but also is beneficial to fast electron transportation. Moreover, the titanium dioxide nanosheets in situ grew on GF, which can inhibit the aggregation of nanosheets and improve the electrochemical kinetics. As freestanding anode material for SIBs, GF-CF exhibits high capacity retention (88.0%) at 50 mA g −1 after 100 cycles and improved rate performance. We also find that ∼45.1% of the total sodium-ion storage comes from capacitive contribution, which could be further improved by diminishing the size of TiO2 nanosheets. The approach of building the desirable coaxial frame structure can be extendedly applied to the architectural construction of electrode materials for other energy devices.